2015
DOI: 10.1007/s00122-015-2615-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci for tuber starch and leaf sucrose contents in diploid potato

Abstract: Key messageMost QTL for leaf sucrose content map to positions that are similar to positions of QTL for tuber starch content in diploid potato.AbstractIn the present study, using a diploid potato mapping population and Diversity Array Technology (DArT) markers, we identified twelve quantitative trait loci (QTL) for tuber starch content on seven potato chromosomes: I, II, III, VIII, X, XI, and XII. The most important QTL spanned a wide region of chromosome I (42.0–104.6 cM) with peaks at 63 and 84 cM which expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 53 publications
(82 reference statements)
2
52
1
Order By: Relevance
“…The DArT map for mch (Śliwka et al 2012a) includes 846 DArT markers and the map for S. ruiz - ceballosii contained 1603 DArT markers (Śliwka et al 2012b). Next three maps were constructed in IHAR–PIB, Młochów and consisted of 1597, 1420, and 1370 DArT markers, respectively (Sołtys-Kalina et al 2015; Śliwka et al 2016; data unpublished, personal communication with Agnieszka Hara-Skrzypiec). The chromosomes richest in markers were chromosomes I (133–230 markers) and II (75–260 markers) in all six analyzed DArT maps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The DArT map for mch (Śliwka et al 2012a) includes 846 DArT markers and the map for S. ruiz - ceballosii contained 1603 DArT markers (Śliwka et al 2012b). Next three maps were constructed in IHAR–PIB, Młochów and consisted of 1597, 1420, and 1370 DArT markers, respectively (Sołtys-Kalina et al 2015; Śliwka et al 2016; data unpublished, personal communication with Agnieszka Hara-Skrzypiec). The chromosomes richest in markers were chromosomes I (133–230 markers) and II (75–260 markers) in all six analyzed DArT maps.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomes richest in markers were chromosomes I (133–230 markers) and II (75–260 markers) in all six analyzed DArT maps. The smallest number of markers was observed on chromosome IV in two maps (Sołtys-Kalina et al 2015; data unpublished, personal communication with Agnieszka Hara-Skrzypiec) (29 and 48 markers), and the map for S. ruiz - ceballosii (74), on chromosome V (86) in the third map (Śliwka et al 2016), on chromosome VII (28) in the mch map, and on chromosome XII (36) in the physical map (Sharma et al 2013). The results of analysis of mch (+) tbr somatic hybrid genomes corresponded well with these data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the method of interval mapping of genomes in a population of diploid potatoes, it was shown that starch phosphorylation is regulated and/or controlled by five quantitative trait loci (QTL) on chromosomes 2, 5 and 9, and the content of amylose by six loci on chromosomes 2, 3, 5, 7 and 10. Similarly, loci controlling the starch grain size, the starch content of potato tuber and the temperature of starch gelatinization were discovered [45,46]. Many of the identified QTLs coincided by their localization with the known genes that encode the enzymes of starch biosynthesis, but, in addition, loci have also been discovered in which no one of the starch biosynthetic genes was previously mapped.…”
Section: Introductionmentioning
confidence: 97%